Reflections on use of Participatory methods in the Capacity Building Program for Tribal Community Health Volunteers - John, Alexander; Gopalakrishnan, Rajani; Javed, Reshma (Indian Journal of Community Health, 2015)
Background: Participatory Rural Appraisal (PRA) constitutes a process of involvement with rural people, for indigenous knowledge building exercises. The effectiveness of such capacity building programs, depends largely on fulfilling objectives which reflect the real needs of the people, while ensuring their participation. As part of a project for self-reliant villages, where community volunteers were trained in various aspects of health, participatory methods were chosen over conventional models of capacity building. Objectives: 1. To develop a model participatory capacity building program for grass root level health functionaries based on participatory need assessment using PRA techniques. 2. To develop an appropriate teaching methodology using participatory learning approaches. 3. To assess the impact of the training program based on pre and post evaluation. Results: The training program based on participatory approach resulted in a statistically significant difference in the knowledge of the volunteers.